2021
DOI: 10.1186/s12967-021-02848-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CPT1a as a prognostic marker can synergistically enhance the antileukemic activity of ABT199

Abstract: Background Fatty acid oxidation (FAO) provides an important source of energy to promote the growth of leukemia cells. Carnitine palmitoyltransferase 1a(CPT1a), a rate-limiting enzyme of the essential step of FAO, can facilitate cancer metabolic adaptation. Previous reports demonstrated that CPT1a acts as a potential molecular target in solid tumors and hematologic disease. However, no systematic study was conducted to explore the prognostic value of CPT1a expression and possible treatment strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Among the increased proteins following RBPMS knockdown, the two ARRB members—ARRB1 and ARRB2—are deregulated in many cancer types and have been linked to the inhibition of the senescence and growth as well as the promotion of the self-renewal, progression, and invasion of cancerous cells [ 39 , 40 , 81 ]. Moreover, CPT1A plays a crucial role in radioresistant and chemoresistant phenotypes in diverse cancer types [ 41 , 42 , 82 ]. Equally, altered protein levels of FLNA, HSPA7, HGF, ERO1A, and GARS1, have been related to cancer migration, adhesion, poor patient prognosis, and metastasis [ 48 , 49 , 50 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the increased proteins following RBPMS knockdown, the two ARRB members—ARRB1 and ARRB2—are deregulated in many cancer types and have been linked to the inhibition of the senescence and growth as well as the promotion of the self-renewal, progression, and invasion of cancerous cells [ 39 , 40 , 81 ]. Moreover, CPT1A plays a crucial role in radioresistant and chemoresistant phenotypes in diverse cancer types [ 41 , 42 , 82 ]. Equally, altered protein levels of FLNA, HSPA7, HGF, ERO1A, and GARS1, have been related to cancer migration, adhesion, poor patient prognosis, and metastasis [ 48 , 49 , 50 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ST1326 demonstrated anti-tumor activity against several leukemia cell lines as well as cells obtained from patients with hematological malignancies [ 275 , 276 ]. Moreover, in AML studies, the synergistic effect of ST1326 with the inhibitor Bcl-2 ABT199 was noted [ 277 ]. Another CPT1 inhibitor with a limited number of scientific reports in the context of anti-cancer activity is oxfenicine (S-4-OH-phenyl-glycine) [ 278 ].…”
Section: The Krebs Cyclementioning
confidence: 99%
“…High-grade serous ovarian cancer (HGSOC) is the most common and lethal form of ovarian cancer, often diagnosed at an advanced stage, and most patients are platinum-resistant (Cannistra, 2004;Matulonis et al, 2016). A recent study in Cell Reports Medicine showed that targeting cpt1a with platinum-based chemotherapy can improve platinum resistance, although the molecular mechanism is currently unclear (Huang et al, 2021).…”
Section: Cpt1mentioning
confidence: 99%
“…Teglicar differs from etomoxir in that it has high selectivity against CPT1A and is reversible, while etomoxir has no significant selectivity against CPT1A and CPT1B and partially inhibits CPT2 (Giannessi et al, 2003). Studies have shown that the combination of ST1326 and ABT199 (Bcl-2 inhibitor) can enhance the anti-acute myeloid leukemia (AML) effect of the latter, indicating that cpt1a may become a potential drug target for the treatment of AML (Ricciardi et al, 2015;Mao et al, 2021). Huntington's disease (HTT) is a severe neurodegenerative disease, and a Drosophila HTT disease model was used to demonstrate that treatment with the cpt1a inhibitor ST1326 can alleviate the symptoms of HTT (Bertapelle et al, 2022).…”
Section: Cpt1mentioning
confidence: 99%